Virtual visits at the Helsinki Head and Neck Center during the COVID-19 pandemic: patient safety incidents and the experiences of patients and staff - Morag Tolvi; Lotta-Maria Oksanen; Lasse Lehtonen; Ahmed Geneid; Pia Männikkö; Hellevi Ruokonen; Anna Majander; Susan Arminen; Leena-Maija Aaltonen (BMC, 2023)
Abstract Background During the COVID-19 pandemic, health care had to find new ways to care for patients while reducing infection transmission. The role of telemedicine role has grown exponentially. Methods A questionnaire on experiences and satisfaction was sent to the staff of the Head and Neck Center of Helsinki University Hospital and to otorhinolaryngology patients treated remotely between March and June 2020. Additionally, patient safety incident reports were examined for incidents involving virtual visits. Results Staff (response rate 30.6%, (n = 116)) opinions seemed to be quite polarized. In general, staff felt virtual visits were useful for select groups of patients and certain situations, and beneficial in addition to face-to-face visits, not instead of them. Patients (response rate 11.7%, (n = 77)) gave positive feedback on virtual visits, with savings in time (average 89 min), distance travelled (average 31.4 km) and travel expenses (average 13.84€). Conclusions While telemedicine was implemented during the COVID-19 pandemic to ensure patient treatment, its usefulness after the pandemic must be examined. Evaluation of treatment pathways is critical to ensure that quality of care is upheld while new treatment protocols are introduced. Telemedicine offers the opportunity to save environmental, temporal, and monetary resources. Nonetheless, the appropriate use of telemedicine is essential, and clinicians must be offered the option to examine and treat patients face-to-face.